Exploring mathematics anxiety among computer science students / Mohd Rizal Razak … [et al.] - Razak, Mohd Rizal; Syed Wahid, Sharifah Norhuda; Ismail, Nor Zalina; Alias, Nursyahidah; Zakariah, Zazaleena (2013)
Mathematics anxiety related with feeling of tension or fear that interferes with math performance. Mathematics anxiety is also called as Mathematic Phobia. The purpose of the study is to determine the Diploma in Computer Sciences students' anxiety level after taking a few mathematical subjects in Universiti Teknologi MARA (UiTM). This study also to check whether gender of students and study technique will influence the students' mathematics anxiety level. To gather the finding, 96 fifth semester Diploma in Computer Sciences (CS110) students were involved in this survey. Most of CS110 has moderate anxiety level. This study also shows that there is no relationship between parents' education level and students' study technique with their anxiety level. This study will provide a useful information for improving the teaching and learning process for mathematic courses in UiTM.